2008
DOI: 10.1021/bi8016087
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Definition of the Biferrous and Biferric Sites in de Novo Designed Four-Helix Bundle DFsc Peptides: Implications for O2 Reactivity of Binuclear Non-Heme Iron Enzymes

Abstract: DFsc is a single chain de novo designed 4-helix bundle peptide that mimics the core protein fold and primary ligand set of various binuclear non-heme iron enzymes. DFsc and the E11D, Y51L and Y18F single amino acid variants have been studied using a combination of near-IR circular dichroism (CD), magnetic circular dichroism (MCD), variable temperature variable field MCD (VTVH MCD) and x-ray absorption (XAS) spectroscopies. The biferrous sites are all weakly antiferromagnetically coupled with μ-1,3 carboxylate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 72 publications
0
39
0
Order By: Relevance
“…38,40 Previous studies have suggested that incorporation of Ala to Gly mutations along the active site channel in DF proteins would decrease steric hindrance of solvent and substrate active site accessibility. One such study 40 showed that the perturbation of DFsc with four Ala to Gly mutations (A10G, A14G, A43G, and A47G), G4DFsc, altered protein reactivity.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…38,40 Previous studies have suggested that incorporation of Ala to Gly mutations along the active site channel in DF proteins would decrease steric hindrance of solvent and substrate active site accessibility. One such study 40 showed that the perturbation of DFsc with four Ala to Gly mutations (A10G, A14G, A43G, and A47G), G4DFsc, altered protein reactivity.…”
Section: Results and Analysismentioning
confidence: 99%
“…Moreover, the resulting biferric form oxidizes substrates, as in natural diiron proteins, but not at appreciable rates. 38,39 By contrast, the biferrous form of G4DFsc catalyzes the O 2 -dependent two-electron oxidation of 4-amino-phenol (4AP). 40 However, the oxidation of 4-aminophenol by G4DFsc appears to be much slower than in the 4-Ala version of the protein, despite the fact that G4DFsc has a less sterically encumbered binding site.…”
mentioning
confidence: 99%
“…985,986 While rapid oxidation of the diferrous center was observed, it was due to an off-pathway iron-tyrosinate complex and not the important diferric intermediate observed for the other diferrous DF proteins. 987,988 Substitution of the four Ala residues to Gly (G4-DFsc) led to the minimization of this complex and a scaffold, which could also catalyze 4-aminophenol oxidation on the same order of magnitude as DFsc was obtained. 989 Most recently, the DeGrado group has shown that a single mutation (from Ile) provides an additional coordinating His residue at the dimetal center of G4-DFsc and results in a protein that can now catalyze the N -hydroxylation of arylamines such as p -anisidine, an activity not detected for G4-DFsc.…”
Section: De Novo Designmentioning
confidence: 99%
“…This strategy has successfully produced both a Zn-binding carbonic anhydrase mimic with activity that approaches that of the native system, as well as a Cu-binding nitrite reductase (CuNiR) mimic. [8] Other successful non-heme redox active de novo constructs include the Due Ferri system [9, 10] and 4Fe-4S clusters. [11, 12] …”
mentioning
confidence: 99%